Pelatihan Koding Dasar dan Game Edukasi Menggunakan Scratch untuk Meningkatkan Kemampuan Berpikir Logis Siswa SD Kelas VI - Wibowo, Asa Hari; Irwan Syahib, Muhammad; Hadistio , Ryan Rinaldi (FAKULTAS TEKNIK UMKENDARI, 2025)
The rapid development of digital technology requires students to acquire logical thinking skills as well as a basic understanding of coding and artificial intelligence from an early age. However, the implementation of coding education at the elementary school level still faces challenges, particularly in the use of appropriate learning methods and media. This community service activity aimed to introduce basic coding concepts and artificial intelligence to sixth-grade elementary school students through the development of educational games using Scratch. The activity was carried out through several stages, including preparation, training implementation, hands-on practice assistance, and evaluation. The learning materials focused on introducing the Scratch interface, basic programming blocks, and the application of if–else logic as a simple decision-making mechanism. The results indicate that students were able to understand fundamental coding concepts, apply simple programming logic, and demonstrate increased interest and enthusiasm for learning technology. In addition, students successfully completed simple game projects based on the given scenarios. This activity contributes positively to enhancing digital literacy and computational thinking skills among elementary school students and can serve as an effective and engaging model for introducing coding and artificial intelligence at the primary education level.